THE SIGNIFICANCE OF SCHOOL-BASED EXPERIENCE FOR EFFECTIVE TEACHING AND LEARNING IN SCHOOLS: A SYSTEMATIC LITERATURE REVIEW - Agyeman, Nana; Aphena, Velapi (Managere: Indonesian Journal of Educational Management, 2023)
This research focuses on improving teacher preparation of students through school-based experiences enhanced by simulation technology and virtual reality. This study aims to understand the impact of the integration of the latest technology in teacher education on their readiness to face new challenges and trends in the growing world of education. This research method uses a systematic literature review to investigate the role and challenges of school-based experiences in student teacher preparation in South Africa. From 265 articles examined in the Scopus database, 13 relevant articles were selected. The results suggest that professional dialogue between student teachers, mentors, and other stakeholders plays a key role in professional development. However, challenges such as lack of time for feedback from mentors and teachers, as well as lack of mentoring, were also identified. The research confirms the importance of school-based experiences in preparing student teachers for the realities of the teaching profession, but also highlights the need to overcome the barriers that stand in the way of such experiences. The implications of this study emphasise the need to enhance mentoring, feedback and professional dialogue in school-based experiences to ensure optimal preparation of student teachers in South Africa.